Altering the substrate specificity of a myofibril‐bound serine proteinase from Crucian carp by site‐directed mutagenesis. Issue 1 (30th July 2018) - Li, Ting; Li, Meng‐Si; Mei, Xue‐Jiao; Sun, Le‐Chang; Liu, Hong; Zhang, Ling‐Jing; Cao, Min‐Jie; Liu, Guang‐Ming
Abstract: BACKGROUND: Myofibril‐bound serine proteinase (MBSP) comprises a class of trypsin‐type serine proteinases that can specifically cleave the carboxyl side of peptide bonds of arginine or lysine residues. To obtain higher specificity MBSPs, mutants were designed based on the substrate‐binding pocket and constructed through site‐directed mutagenesis. RESULTS: The wild‐type (WT) and mutants were expressed in Pichia pastoris, and its enzymatic properties indicated that the mutants D170S, D170T, D170K and D170T/G203A were not biologically active. However, S171A specifically cleaved arginine residues and G203A preferably hydrolyzed lysine residues. The secondary structures of mutants were approximately similar to that of the WT according to the results of circular dichroism spectroscopy. Additionally, molecular docking showed that substrates were able to combine with S171A within the critical areas through hydrophobic interaction, hydrogen bonds and van der Waals electrostatic force. CONCLUSION: The structural stability of MBSP was consistent using amino acid substitution. Due to the interaction pattern of substrates and mutant enzyme changes, only S171A was selective in cutting Arg residues, which illustrates how the catalytic triad and substrate‐binding pocket of MBSP plays an important role during enzymatic hydrolysis of substrates. © 2018 Society of Chemical Industry